Programa educativo "Sembrando Amistad" y su influencia en las relaciones interpersonales de los niños y niñas de 5 años de la Institución Educativa Nº 288 "Ana Sofía Guillena Arana" del distrito de Rioja, 2013 - Uriarte Quiroz, Nancy (2013)
The purpose of this investigation was to apply the educational program "Sowing Friendship" to enhance the interpersonal relationships of children 5 years of School Nº 288 "Ana Sofia Arana Guillena" Rioja district, 2013. To meet the objectives, based on the studies of the history of research in interpersonal theory of psychiatry, social learning theory, trower theory, multiple intelligences theory and the theory of emotions. Such theoretical framework allowed to raise the following hypothesis: Education Program "Sowing Friendship" significantly improve interpersonal relationships children 5 years of School Nº 288 "Ana Sofia Arana Guillena" Rioja district 2013. The research design was pre test and post test with a single group, which belongs to the pre experimental design. The sample consisted of 27 children from five years of School Nº 288 "Ana Sofia Guillena Arana", data collection was conducted through an observation sheet of interpersonal relations that measured empathy and social skills, same that was applied before and after 13 develop learning sessions. In the analysis of results was determined that the educational program "Sowing Friendship" significantly improves interpersonal relationships of children 5 years of School Nº 288 "Ana Sofia Guillena Arana" district of Rioja, 2013, with calculated value (tk: -14,00) less than the tabulated value (tt: -1 . 721 ). To increase the level of highly negative relationships in the pretest to 54,55%, positive interpersonal relationships in the post with 50%.